2022
DOI: 10.1186/s12888-022-04037-4
|View full text |Cite
|
Sign up to set email alerts
|

Migration modulates the prevalence of ASD and ADHD: a systematic review and meta-analysis

Abstract: Background Migration has been implicated as a risk factor for autism spectrum disorder (ASD) and attention-deficit/hyperactivity disorder (ADHD), but evidence is still limited and inconsistent. We aim to investigate the relationship between migration status and risk of ASD and ADHD. Methods Electronic databases including PubMed, EMBASE, Web of Science, and PsychINFO were searched to identify observational studies on this topic, from inception to Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…This was also found in a population-based Australian study that investigated the prevalence of developmental disabilities, finding that the impact of maternal migration acted in two ways—it increased the likelihood factor of diagnosis with autism with ID for children of non-Australian-born women from low- and middle-income countries, but was also as a protective factor for children of non-Australian-born mothers for diagnosis of developmental disabilities overall [ 19 ]. This was further evident in a 2022 systematic review on migration and autism prevalence, which found maternal migration increased the likelihood of an autism diagnosis, with migrant autistic children more likely to also be diagnosed with co-occurring ID [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…This was also found in a population-based Australian study that investigated the prevalence of developmental disabilities, finding that the impact of maternal migration acted in two ways—it increased the likelihood factor of diagnosis with autism with ID for children of non-Australian-born women from low- and middle-income countries, but was also as a protective factor for children of non-Australian-born mothers for diagnosis of developmental disabilities overall [ 19 ]. This was further evident in a 2022 systematic review on migration and autism prevalence, which found maternal migration increased the likelihood of an autism diagnosis, with migrant autistic children more likely to also be diagnosed with co-occurring ID [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to current estimates, ASD affects up to 1 in 36 children worldwide, and 75% of those children also have one or more co-occurring mental health conditions, such as attention-deficit hyperactivity disorder, bipolar disorder, depression, or anxiety 3 . It has been observed that several hereditary variables, such as parental age, maternal stress, smoking, exposure to certain drugs, and improper brain development during pregnancy may raise the chance of ASD in developing children 4 . Moreover, low birth weight, metal exposure, and a sibling with autism also account for a high risk of developing ASD 5 .…”
mentioning
confidence: 99%
“…Research has suggested that migrant parents are more prone to having ASD in their children than non-migrants 4 . A study by Mughal et al 6 , concluded that children of immigrants exhibit unpleasant behavior when exposed to geographic differences because they have weaker or less adaptive abilities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is a documented dearth of ASD studies among immigrants and minority groups in HICs [ 27 ]. Hence, the evidence supports ethnic and racial variances in ASD prevalence and access to services, even among the HICs and developed societies.…”
mentioning
confidence: 99%